BS EN 60502-2 AMD1. Power cables with extruded insulation and their accessories for rated voltages from 1 kV (Um = 1, 2 kV) up to 30 kV (Um = 36 kV). Part 2. Cables for rated voltages from 6 kV (Um = 7, 2 kV) up to 30 kV (Um = 36 kV (22nd November 2021) - British Standards Institution,
No abstract available